evolution of vaccination coverage and the covid-19 pandemic impacts on routine immunization targets for children under one years old in brazilian northeast. (Revista Brasileira Multidisciplinar, 2025)
Vaccination is essential for preventing infectious diseases, representing a cost-effective health investment. However, vaccine coverage in Brazil has declined in recent years, particularly during the COVID-19 pandemic, leading to the resurgence of preventable diseases, as well as delays in the childhood vaccination schedule. In this sense, this study aimed to analyze the evolution of vaccine coverage and the impacts of the COVID-19 pandemic on routine immunization goals in children under 1 year of age in the Northeast region of Brazil between 2013 and 2021. This was an ecological and observational study that used secondary data (SINASC, SI-PNI, IDH-IBGE), as well as the In-Loco Social Isolation Index (IIS), to determine annual vaccine coverage rates, as well as possible correlations using the linear regression method. The results showed that 6 out of 8 vaccines reached vaccination targets in 2013, only 3 in 2016, and no vaccine reached the target during the pandemic. The correlation between the IIS and vaccine coverage was significant (p
Keywords: childhood vaccination; immunization rates; vaccine hesitancy; covid-19; social isolation.